Odpowiedzi

Najlepsza Odpowiedź!
2009-11-22T02:24:00+01:00
1. W(x)=x³-1
P(x)=2x²+4x+1
a)U(x)=W(x)+P(x)
U(x)=x³-1+2x²+4x+1
U(x)=x³+2x²+4x
Stopnień 3
b)U(x)=W(x)-P(x)
U(x)=x³-1-(2x²+4x+1)
U(x)=x³-1-2x²-4x-1
U(x)=x³-2x²-4x-2
Stopień 3
c)U(x)=3W(x)-4P(x)
U(x)=3(x³-1)-4(2x²+4x+1)
U(x)=3x³-3-8x²-16x-4
U(x)=3x³-8x²-16x-7
Stopień 3
d)U(x)=2W(x)-xP(x)
U(x)=2(x³-1)-x(2x²+4x+1)
U(x)=2x³-2-2x³-4x²-x
U(x)=-4x²-x-2
Stopień 2
e)U(x)=W(x)+(1-x)P(x)
U(x)=x³-1+(1-x)(2x²+4x+1)
U(x)=x³-1+2x²+4x+1-2x³-4x²-x
U(x)=-x³-2x²-3x
Stopień 3
f)U(x)=2[W(x)]²+P(x)/2
U(x)=2[x³-1]²+(2x²+4x+1)/2
U(x)=2[x⁶-2x³+1]+x²+2x+½
U(x)=2x⁶-4x³+2+x²+2x+½
U(x)=2x⁶-4x³+x²+2x+2½
Stopień 6
-----------------------------------------------------------------------------
2.
a)(1+2x)(1-2x)
1-4x²
b)(3x²-1)²
9x⁴-6x²+1
c)(x+⅓)³
x³+x²+⅓x+1/27
d)(1-2x)³
1-6x+12x²-8x³
-8x³+12x²-6x+1
e)(1-x)(1+x)(1+x²)
(1-x²)(1+x²)
1-x⁴
f)(√2x-1)(2x²-1)(√2x+1)
(√2x-1)(√2x+1)(2x²-1)
(2x²-1)(2x²-1)
(2x²-1)²
4x⁴-4x²+1
g)(2x+1)(4x²-2x+1)
8x³+1
h)(x-2)(x²+2x+4)(x³+8)
(x³+8)(x³+8)
(x³+8)²
x⁶+16x³+64
-----------------------------------------------------------------------------
3.
a)x³+3x
x(x²+3)
b)3x⁴-3x²
3x²(x²-1)
3x²(x-1)(x+1)
c)2x³+4x²+2x
2x³+2x²+2x²+2x
2x²(x+1)+2x(x+1)
(2x²+2x)(x+1)
d)x⁶+7x⁵+6x⁴
x⁶+x⁵+6x⁵+6x⁴
x⁵(x+1)+6x⁴(x+1)
(x⁵+6x⁴)(x+1)
x⁴(x+6)(x+1)
e)x³-x²+x-1
x²(x-1)+1(x-1)
(x²+1)(x-1)
f)x³-2x²-2x+4
x²(x-2)-2(x-2)
(x²-2)(x-2)
(x-√2)(x+√2)(x-2)
g)x⁴+x³-4x²-4x
x³(x+1)-4x(x+1)
(x³-4x)(x+1)
x(x²-4)(x+1)
x(x-2)(x+2)(x+1)
h)5x³+x²-15x+3
x²(5x-1)-3(5x-1)
(x²-3)(5x-1)
(x-√3)(x+√3)(5x-1)
-----------------------------------------------------------------------------
5.
a) a=-3*3³+4*3²+3-1
a=-3*27+4*9+2
a=-81+36-2
a=-43
b=-3*(-1)³+4*(-1)²-1-1
b=-3*(-1)+4-2
b=3+4-2
b=5
c=-1 (Wszystkie x się zerują)
b)a=(1/9)*3⁴-(1/6)*3²-3-½
a=(1/9)*81-(1/6)*9-3-½
a=9-4½-3-½
a=1
b=(1/9)*(-1)⁴-(1/6)*(-1)²+1-½
b=(1/9)*1-(1/6)*1+1-½
b=(1/9)-(1/6)+1-½
b=(4/9)
c=-½ (Wszystkie x się zerują)
-----------------------------------------------------------------------------
6.
a)|(-1)³+p(-1)²-4*(-1)+q=4
|q=3 (Wszystkie x oraz p się zerują)

|-1+p+4+3=4
|q=3

|p=-2
|q=3

b)|-p(-1)³+3*(-1)²-1-6q=4
|-6q=3 (Wszystkie x oraz p się zerują)

|p+3-1-6q=4
|q=-½

|p+3-1+3=4
|q=-½

|p=-1
|q=-½